Investigation for the Effects of Omega Fatty Acid and Glutamine-L-Alanine on Morbidity and Mortality in the Critically ILL Patients after Major Abdominal Surgery - Kaya Bulut Gulsen; Ozgultekin Asu; Turan Guldem; Isıtmangil Gulbu; Terzioglu Ufuk; Kurt Nurettin; Ekinci Osman (Journal of Pharmacy and Nutrition Sciences, 2014)
Background & Objectives: This study investigated the effects for the addition of omega 3 fatty acids and glutamine-L-alanine to the standard enteral and/or parenteral nutrition regimen on infection and mortality in the critically ill patients after major abdominal surgery. Methods: This is a prospective, randomized, single center study. A total of 43 patients (age range: 18-85 years), who were in the critical care unit after major abdominal surgery, were included. Patients were divided into two groups according to simple randomized selection [Control group, n=20; Study Group, n=23 (omega3 fatty acids and glutamine-L-alanine)] and were monitored for 21 days. Patients were examined for the assessment of APACHE II Score and existence of ALI (acute lung injury)/ARDS (acute respiratory distress syndrome) requiring mechanical ventilation. In addition to standard enteral or parenteral nutrition, patients in the study group were given parenteral pharmaconutrition products for 10 days postoperatively. Groups were compared for the duration of mechanical ventilation, duration of stay in the intensive care unit and hospitalization, and mortality. Laboratory parameters including CRP, TNF, IL6, IL8, nitrogen balance, albumin, and total lymphocyte count were recorded. Results:Although the mean APACHE score was higher in study group in which patients received omega-3 fatty acids and glutamine-L-alanine support, the clinical infection rate seemed to decrease insignificantly. Conclusions: A clinically decreased rate of infection was observed in patients with a high APACHE II score, or who received omega-3 fatty acids, glutamine-L-alanine, are required to be administered more selectively and in larger patient groups in different doses and in combination protocols in accordance with the current pharmaconutritional support and in different timing combinations, including preoperative period